Implementing Spanish-language pesticide labeling: The role of internet access for migrant and seasonal farmworkers - LePrevost, Catherine; Lee, Joseph; Moore, Modjulie (Journal of Agriculture, Food Systems, and Community Development, 2025)
Mitigating pesticide exposure among migrant and seasonal farmworkers (both referred to as “farmworkers” herein) is important for agricultural safety and health. Among farmworker patients served by the North Carolina (NC) Farmworker Health Program in 2021 (N = 11,518), 99% identified as Latine, 98% reported being nonfluent in English, 94% reported incomes below the federal poverty level, and 92% indicated they were uninsured. Prior community-led work in NC with farmworkers, advocates, and others working closely with farmworkers has highlighted demands for expanded employment benefits and improved living and working conditions, including pesticide protections, as well as expanded access to high-quality health care, improved visibility of farm work, and policy change for a better future (Cofie et al., 2023). Efforts to address pesticide exposure are critically important. . . .